Physical Education Teachers' Perceptions Of The Implementation Of The Independent Curriculum In Junior High Schools Across Central Bengkulu Regency - Febi Puspasari; Suwarni Suwarni; Martiani Martiani (Universitas Dehasen Bengkulu, 2026)
This study aims to examine the perceptions of Physical Education (PJOK) teachers regarding the implementation of the Independent Curriculum (Kurikulum Merdeka) in junior high schools across Central Bengkulu Regency. In this context, perception refers to the teachers' viewpoints and attitudes toward the Independent Curriculum, which is currently being intensively promoted within Indonesia’s education system. This research adopts a quantitative descriptive approach using a survey method. The population of the study consists of all PJOK teachers at junior high schools in Central Bengkulu Regency. The sampling technique used is total sampling, involving 32 PJOK teachers. Data were collected using a questionnaire that measured variables related to perception and the Independent Curriculum, employing a Likert scale. The analysis results indicate that the overall perception of PJOK teachers toward the implementation of the Independent Curriculum in junior high schools throughout Central Bengkulu Regency falls entirely within the moderate category (100%), with no respondents falling into the very high, high, low, or very low categories.